BACTERIAL CONSORTIA FOR RETTING OF COCONUT HUSKS IN TANKS - Anita Das Ravindranath; Saroi Bhosle (International Coconut Community Journal, 1999)
A bacterial consortium developed on coconut husk leachates could ret coconut husk steeped for retting in rap water in a period of three months. The quality of the coir fibre obtained was comparable to traditionally retted fibre. The consortia could also bestow a greater degree of softness to the mechanically extracted coir fibre. Coir extraction can therefore be practiced by supplying the consortia for retting of husk for production of fibre and enhance the commercial utilization of the husk in coconut growing regions of Asia.